The learning, compliance, and psychological costs of applying for the Disability Support Pension. Issue 4 (19th October 2021) - Collie, Alex; Sheehan, Luke; McAllister, Ashley; Grant, Genevieve
Abstract: The Disability Support Pension (DSP) provides financial support to more than 750, 000 Australians with permanent physical, intellectual or psychiatric impairments that prevent them from engaging in employment. We sought to characterise the information, compliance and psychological costs of applying for the DSP. A cohort of 518 DSP applicants and recipients completed a questionnaire capturing medical, disability, benefit and demographic data. The questionnaire also included an Administrative Burden (AB) scale that was co‐developed with disability advocates and people with lived experience of DSP processes. Most respondents reported high or very high scores on three sub‐scales assessing information, compliance and psychological costs. In logistic regression models, DSP applicants reported greater costs than DSP recipients across all three scales. People with poorer health‐related quality of life, younger age and less education reported higher costs, consistent with the observation of an inequitable distribution of administrative burden in AB theory. All three scales had acceptable reliability. Study findings suggest that DSP applicants find the application process challenging and stressful. These effects are more pronounced in people who have applied for the DSP than those currently receiving the DSP, and in those with lower human capital. Abstract : Australians applying for or receiving the Disability Support Pension (DSP) experience high learning, compliance and psychological costs associated with DSP application processes and interaction with the social security agency Centrelink. These administrative burdens are not evenly distributed, as people with lower levels of human capital report greater costs.